2015
DOI: 10.1007/s10620-015-3579-y
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Corticotropin-Releasing Factor Receptor Type 2 Activation Increases Colonic Blood Flow Through Nitric Oxide Pathway in Rats

Abstract: Background Corticotropin-releasing factor (CRF) peptides exert profound effects on the secretomotor function of the gastrointestinal tract. Nevertheless, despite the presence of CRF peptides and receptors in colonic tissue, their influence on colonic blood flow (CBF) is unknown. Aim To determine the effect and mechanism of members of the CRF peptide family on CBF in isoflurane-anesthetized rats. Methods Proximal CBF was measured with laser Doppler flowmetry simultaneously with mean arterial blood pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Loss of CRHR2 leads to increased inflammation, delayed healing, and exacerbates the inflammatory insult [ 47 49 ]. Akiba et al reported that peripheral CRHR2 activation induces colonic hyperemia through nitric oxide synthesis without involving prostaglandin synthesis or sensory nerve activation and may protect the colonic mucosa [ 50 ]. In a recent study, low grade inflammation was observed in the colonic mucosa of IBS patients [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of CRHR2 leads to increased inflammation, delayed healing, and exacerbates the inflammatory insult [ 47 49 ]. Akiba et al reported that peripheral CRHR2 activation induces colonic hyperemia through nitric oxide synthesis without involving prostaglandin synthesis or sensory nerve activation and may protect the colonic mucosa [ 50 ]. In a recent study, low grade inflammation was observed in the colonic mucosa of IBS patients [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is believed to involve the peripheral neurons and the spinal cord as increased activity of inferior splanchnic nerve and phosphorylation of Erk in laminae II and I were recorded. Another mechanism that may contribute to the inhibitory role of CRF 2 is by inducing colonic hyperemia through nitric oxide pathway upon activation5 [129]. However, other studies indicate that both CRF receptors contribute to the visceral pain by increasing the epithelial permeability, as mentioned above.…”
Section: Peripheral Modulation Of Visceral Pain By Crf-crfr Systemmentioning
confidence: 97%
“…In vivo, the effects tend to vary according to the species and vascular bed. In rats, several studies have shown consistent dose-dependent decreases in blood pressure (BP) after Ucn-2 infusion [51,[42][43][44]52]. In this specie, Ucn-2 appears to induce marked mesenteric vasodilatation, while it produces an inconsistent renal vasodilation, indicating less powerful coupling of CRF-R2 receptors in the renal vascular bed.…”
Section: ) Vascular Effects A) Animal Studiesmentioning
confidence: 99%